Book Review: Invaluable Contribution to the Treasury of Translation Science - Andrienko, Tatiana (Lesya Ukrainka Volyn National University, 2020)
This year, 2020, has been marked by an outstanding event, long awaited by scholarly, linguistic, and literary community: Volume 1 of Translation Encyclopedia edited by Oleksandr Kalnychenko and Leonid Chernovaty was published in Ukrainian by Nova Knyha Publishers, Vinnytsia, Ukraine. The book has seen light thanks to the leadership of the Ukrainian Translator Trainers’ Union (UTTU) headed by Dr. Leonid Chernovaty, as well as talents and efforts of a highly qualified team of translators and translation professors from major universities of Ukraine. It comprises a translation of The Handbook of Translation Studies (edited by Yves Gambier, Luc van Doorslaer, John Benjamins Publishing Company, 2010). By the depth of insights into problems, the variety of addressed topics, clarity and persuasiveness of argumentation, openness to innovation, as well as historical and geographical frameworks the reviewed book is definite to find its place among the major humanitarian publications, considerably broadening the horizons of Ukrainian scholars, students, and thinkers. The collection presents a wide range of articles summarizing the newest concepts and trends of Translation Studies, such as adaptation, self-translation, censorship, community and conference interpreting, technical translation, terminology and translation, multilingualism and translation, etc. Through the authors’ perspectives, the reader may follow the dynamics of changes in the content of translation science and its various approaches (descriptive, applied, interpretive, cognitive, functional) and its major concepts (such as translation quality, relevance, norms, units, strategies and tactics). Of great interest to the audience will be the scope of interdisciplinary fields, such as history of translation, translation didactics, ethics of translation, as well as articles unveiling the links of translation studies with semantics, semiotics, philosophy, hermeneutics, journalism, gender factors, ethics, sociology, ethnography and art. The Encyclopedia also embraces such fields of literary translation as postcolonial literature, censorship, children's literature, translating plays, humor and comics; it outlines the problems of industry-specific (political, technical, commercial, scientific, religious, legal translation, media interpreting) and even sign language translation. Much attention is devoted to practical applications of the latest translation research, as well as new technologies in translation, research and teaching translation methodologies, as well as the role of translation in foreign language teaching. The concepts and ideas in the book are presented by the outstanding translation theorists, many of whom are the authors and conceivers of new theories of translation and their major research fields: Fabio Alves & Amparo Hurtado Albir, Jorge Díaz Cintas, Riitta Jääskeläinen, Marianne Lederer, Jeremy Munday, Christiane Nord, Franz Pöchhacke, Christina Schäﬀner and others. A valuable feature of the ideas covered in the Encyclopedia is their openness to plurality of scholarly opinions, continuous dialogue over the major problems of translation theory and practice, which involves the reader into discussion and inspires the further search for solutions. The translation of the original theoretical insights into Ukrainian by seasoned scholars, professional translators and translation teachers will, first and foremost, open them to a broader audience, making their content more accessible and perceivable to the readers. But what is more important, it develops the conceptual network of translatology, enriching the Ukrainian terminology, and expanding the borders of the Ukrainian language scientific style. Besides being an invaluable source of theoretical knowledge, the book is also an exemplary application of theory into practice, a guide to the state-of-art choice of translation strategies, tactics and decisions, a model scientific translation to be emulated by practicing and aspiring translators. The 1st volume of Translation Encyclopedia, edited by Oleksandr Kalnychenko and Leonid Chernovaty will definitely find equally high acclaim of professors and students, theorists and practitioners, seasoned and aspiring scholars of translation and relevant fields. Welcoming the new pioneering publication, we strongly believe that it will initiate a tradition of publishing translated scholarly works in Ukraine, and look forward to the appearance of new volumes.